GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 2476 species occurrences available in GBIF matching the query: TaxonKey: Gopherus agassizii Cooper, 1863. The dataset includes 2476 records from 52 constituent datasets: 9 records from Database Schema for UC Davis Wildlife museum. 27 records from SBMNH Vertebrate Zoology. 1106 records from MVZ Herp Collection (Arctos). 1 records from UNR Herpetology. 1 records from Paleobiology Database. 33 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 2 records from Bernice P. Bishop Museum. 1 records from MPM Herpetology. 10 records from CM Herps Collection. 4 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 2 records from UWBM Herpetology Collection (Arctos). 52 records from Herp Collection. 50 records from herpetology. 5 records from Reptile Specimens. 106 records from University of California Museum of Paleontology. 4 records from Coleccion de Herpetologia, MZFC-UNAM. 6 records from UTEP Vertebrates. 4 records from Colección Herpetológica del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 3 records from Oregon State University Herpetological Collection. 33 records from SDNHM Herpetology Collection. 2 records from MSUM Ichthyology and Herpetology Collections. 3 records from Herp specimens. 66 records from iNaturalist research-grade observations. 1 records from UC Davis Department of Anthropology Museum. 19 records from Herps Specimens. 46 records from LACM Vertebrate Collection. 6 records from SMNS Herpetologie. 6 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 66 records from Herpetology Collection. 14 records from Museum of Comparative Zoology, Harvard University. 540 records from NatureServe Network Species Occurrence Data. 17 records from KUBI Herpetology Collection. 9 records from New Mexico Biodiversity Collections Consortium database. 2 records from UTA Herpetology. 1 records from Collection Herpetologie - SNSD. 2 records from Inventario nacional de especies vegetales y animales de uso artesanal. 6 records from CUMV Reptile Collection (Arctos). 30 records from AMNH Herpetology Collections. 55 records from NMNH occurrence DwC-A. 1 records from FHSM Herps Collection. 1 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 1 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 62 records from CAS Herpetology (HERP). 6 records from UMMZ Herpetology Collection. 4 records from Herpetology. 2 records from RBINS collections. 25 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3 records from TNHC Herpetology Collection. 3 records from UCM Amphibian and Reptile Collection (Arctos). 11 records from Herpetology Collection. 6 records from CCBER Herpetology Collection. 1 records from Cowan Tetrapod Collection - Herpetology.
Keywords: GBIF; biodiversity; species occurrences